Simulasi Dan Pemodelan Software Defined Network (SDN) Untuk Manajemen Jaringan Data UR - Rian Arighi Mahan; Linna Oktaviana Sari; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Computer Network is the fundamental part of telecommunication. Computer network has been developed to fulfill the needs of humanity. Nowadays, the centralized network is needed to control the network traffic easily. Software Defined Network (SDN) is centralized network that provide the separated data plane and control plane in different system. This study provides the network Universitas Riau (UR) with SDN. The mininet was used to design and simulate UR design network using SDN. Theresult shows that the simulated network has the delay value of 0.506 ms. Compared to delay of UR existing network value of 13.874 ms, the simulated network provides a better performance than the existing network. In conclusion, SDN can be considered to implemented in UR network because its delay value is less than ITU standard 150 ms and less than existing network.Keywords : Network, Centralized, SDN, Delay.